EFICÁCIA ADAPTATIVA DE MULHERES E HOMENS INSERIDOS NUM PROGRAMA DE FERTILIZAÇÃO IN VITRO - Corrêa, Káthia Regina Ferreira D`campos (2004)
The aim of this work was to characterize a sample of patients inserted in an in vitro fertilization programme; evaluate the adaptive efficacy of men and women inserted in this programme; analyze two representative clinical cases of the sample, regarding micro and macro indicant factors of psychological adaptation. The data were collected in a Center of Human Reproduction, where 65 men and 65 women were selected, in the period of March to October of 2002, and characterized according to social-economical-cultural data. 57 pairs were extracted: 57 men and 57 women diagnosed by Operationalized Adaptive Diagnostic Scale, representing the greatest concentration of cases with the following medical diagnosis: infertile women and fertile men. Afterwards, two cases were selected (a man and a woman) who represented this group; they were studied in clinical, and qualitative analysis according to the presuppositions of the adaptation theory. The men were found between the ages of 23 and 56, and the women from 23 to 45. Regarding the diagnosis, there were the following concentrations: the men (64.9%) were classified in Group 2 Light Ineffective Adaptation and the women (52.6%) in Group 4 Severe Ineffective Adaptation. During the diagnosis, it was revealed that 20.2% of the subjects were in crisis: 8.8% of the men and 31.6% of the women. In the representative report case, where the men (group 2) showed a better adaptive condition than their spouses (group 4), it was verified that the adequacy of the men in the sectors was: Affective-Relational not very appropriate answer; Productivity appropriate answer; Social-Cultural appropriate answer and Organic appropriate answer. Their spouses, in the meantime, diagnosed as group 4 Severe Ineffective Adaptation without crisis, showed very little appropriate answer on Affective-Relational sector, and not very appropriate answer on Productivity, Social-Cultural and Organic sectors. We have come to the conclusion that the men who took part of this sample had a better adaptive efficacy compared to the women during the in vitro fertilization process. There is a need of preventive psychological attendance up against a possible start of crisis, and specific interventions to the crisis moment.